Peran Gereja Mewujudkan Tanggung Jawab Sipil Pembangunan Karakter Bangsa - Yakob Tomatala (Sekolah Tinggi Teologi Jaffray Jakarta, 2019)
The Church as the People of the LORD God have integral responsibility. This integral responsibility has holistic natures related to various aspects in life. Civil responsibility is one of the responsibility of the church. All of the church civil responsibility is closely related to the total development of the society and the nation to the larger extent. The foundation of church civil responsibility is developing the feeling of being one nation as part of character development being held in the community development. The specific focus of developing the feeling of being one nation in essence is to strengthen nation identity. The character development is tightly related to national education as a tool to achieve such noble end. This research is based on the ideal to help the church in cooperation with the nation wide societies to be involved in the national development of character building ot its community.